2020
DOI: 10.1021/acssuschemeng.0c00524
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transfer Hydrogenolysis of Bio-Polyols to Renewable Chemicals over Bimetallic PtPd/C Catalysts: Size-Dependent Activity and Selectivity

Abstract: Most industrial hydrogenation processes are conducted under elevated temperature and pressure. Catalytic transfer hydrogenation/hydrogenolysis, in the absence of externally added hydrogen, is known to be much more energy efficient and atom economical. However, the multifunctional nature of catalyst structure on simultaneous hydrogen generation, hydrogen transfer, and hydrogenation reactions is largely unexplored. We reported a design principle and size-dependent behavior of bimetallic PtPd/C catalysts for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The mass flow rates for PG, EG, acetol, and PrOH are 893.4 kg/h, 89.3 kg/h, 14.1 kg/h, and 12.3 kg/h, respectively, while CTH of glycerol leads to 606.3 kg/h, 42. kg/h, and 116.6 kg/h for those products. The product distribution (carbon-based selectivity, 58.7%) ( Zhang et al, 2020a ; Yin et al, 2020 ) for the two processes has also been presented in inset of Figure 4 . It is found that, for CHDO process, the main products include PG (86.5%) and EG (10.6%), with trace amounts of acetol and PrOH as co-products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mass flow rates for PG, EG, acetol, and PrOH are 893.4 kg/h, 89.3 kg/h, 14.1 kg/h, and 12.3 kg/h, respectively, while CTH of glycerol leads to 606.3 kg/h, 42. kg/h, and 116.6 kg/h for those products. The product distribution (carbon-based selectivity, 58.7%) ( Zhang et al, 2020a ; Yin et al, 2020 ) for the two processes has also been presented in inset of Figure 4 . It is found that, for CHDO process, the main products include PG (86.5%) and EG (10.6%), with trace amounts of acetol and PrOH as co-products.…”
Section: Resultsmentioning
confidence: 99%
“…Reaction parameters such as temperatures, pressures, and catalyst loading have been studied experimentally in our laboratory, as already reported previously ( Jin et al, 2019a ; Jin et al, 2019b ; Zhang et al, 2020a ; Zhang et al, 2020b ; Yin et al, 2020 ). Conversion and selectivity data obtained from those reports were used as input for determination of configuration of reactor unit in simulation ( Von Held Soares et al, 2017 ; Zhang et al, 2020a ; Yin et al, 2020 ). As shown in Table 1 , the reactions considered for this work include 1) dehydrogenation of EtOH, 2) dehydration of glycerol, and (3–4) hydrogenolysis of glycerol.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…To enhance selectivity, many monometallic catalysts based on Cu, Ni, Pt or Ru were developed and tested in combination with a homogeneous base [8–14] . Additionally, recent research focused on the development of bimetallic catalysts to facilitate reactions with the addition of a solid base, without external hydrogen pressure or to further enhance selectivity [15–24] …”
Section: Introductionmentioning
confidence: 99%